Pengaruh Job Insecurity, Kepuasan Kerja Dan Komitmen Organisasi Terhadap Turnover Intention (Studi Pada Perusahaan Daerah Air Minum/PDAM Kota Bima) - Sisi Purwati; Abdul Kodir Djaelani; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study ains to determine and analiyze the effect of Job Insecurity, Job Satisfaction and Organizational Commitment on Turnover Intention at Regional Drinking Water Company/PDAM Kota Bima aither partially or simultaneously. This research was conducted using a questionnaire distributed though random sampling technique wit a sampel of 66 people who are amployees of the Ragoinal Drinking Water Company/PDAM Kota Bima. Data analysis in this study used SPSS (statistical product and service sulation)The results of this study indicate that the first result of job insecurity partially affects turnover intention. The second result of job statisfaction partially affects turnover intention. meanwhile, simultaneously job insecurity, job statisfaction and organizational commitment have a signigicant affect on turnover intention. Keywords: Job Insecurity, Job Satisfaction, Organizational Commitment, and Turnover Intention